Needs Analysis on Developing Mobile-Phone Based Learning Materials to Accelerate Studentsâ€™ Mastery of English Vocabulary - Sugesti, Nunik; Sugirin, Sugirin; Priyana, Joko; Wulandari, Ella (JOLLT Journal of Languages and Language Teaching, 2023)
Due to their important role of a skilled and productive workforce for the nation's economy and progress, vocational high school graduates need special attention and efforts to improve their quality, including the English communication skill to support the mastery of their area of expertise. Their English mastery is greatly influenced by their mastery of vocabulary. So, developing mastery of English vocabulary needs to be done with various efforts, including utilizing information technology services in the form of mobile phone-based learning materials. In line with this, this research was aimed at conducting needs analysis on developing such materials. Â The data were collected by using three questionnaires distributed to 76 students of Mechanical Engineering of vocational high schools, 13 English teachers from 6 vocational high schools, and 7 respondents who were vocational high school graduates in five districts/cities in Special Region of Yogyakarta. The research employed the quantitative (descriptive statistics) and qualitative data analysis (interactive analysis techniques). The results of data analysis, which included the list of required vocabulary, forms of activities, and other aspects that reflected the ways how the materials were presented, were then used as a basis for preparing the syllabus, grid, and initial draft of teaching materials.The data also included the types of services offered by the mobile-phone learning.